Bifidobacterium animalis subsp. lactis LKM512 reduces levels of intestinal trimethylamine produced by intestinal microbiota in healthy volunteers: A double-blind, placebo-controlled study - Mitsuharu Matsumoto; Yusuke Kitada; Yumi Shimomura; Yuji Naito (Journal of Functional Foods, 2017)
Previous clinical studies on the prevention of atherosclerosis with probiotics aimed only for the reduction of blood lipids. The aim of this study was to investigate the effect of probiotic Bifidobacterium animalis subsp. lactis LKM512 on colonic trimethylamine (TMA) and atherosclerosis-related markers in healthy subjects. Twenty-seven subjects (average age, 47.1 years) were assigned to receive probiotics or placebo for 12 weeks. At week 12, the fecal TMA concentration and BMI in the probiotics group was lower than that in the placebo group (p < 0.05) and the relative abundance of specific bacterial groups (Clostridia, Clostridiales, and Lachnospiraceae), including TMA-producing bacteria, in the probiotics group was lower than that in the placebo group (p < 0.05). The serum TNF-α concentration decreased (p < 0.01) in the probiotics group only. Thus, probiotic LKM512 could reduce the risk of arteriosclerosis development in healthy subjects via reduction of TMA produced by intestinal microbiota.